Predictive Analytics and Strategic Banking Performance: The Critical Impact of Organizational Readiness - Utomo, Bekti; Wahidah, Nurul Jannatul; Wisudawati, Tri (Novatio : Journal of Management Technology and Innovation, 2025)
Predictive analytics (PA) has become a cornerstone of digital transformation in banking, offering tools for improved decision-making across risk, marketing, and operations. This study investigates the moderating role of organizational readiness—comprising infrastructure, talent, and culture—on the relationship between PA adoption and strategic performance in banks. A cross-sectional survey of 50 banking institutions was conducted, measuring predictive analytics usage, organizational readiness scores, and key financial performance indicators such as Return on Assets (ROA), Non-Performing Loans (NPL), and cost-to-income ratios. Using hierarchical regression and interaction analysis, findings reveal that while PA adoption positively influences strategic performance, its impact is significantly enhanced in institutions with high organizational readiness. Institutions with stronger infrastructure, better-trained staff, and supportive analytics cultures reported higher returns from analytics initiatives. These results underscore the importance of socio-technical alignment in unlocking the full potential of predictive analytics. Banks are encouraged to view PA not as a standalone technological tool but as part of a broader transformation requiring cultural, structural, and strategic integration.